Development of Electrochemical Nanosensor for the Detection of Malaria Parasite in Clinical Samples - Obisesan, Olaoluwa R.; Adekunle, Abolanle S.; Oyekunle, John A. O.; Sabu, Thomas; Nkambule, Thabo T. I.; Mamba, Bhekie B. (Frontiers in Chemistry, 2019)
In this study, electrochemical nanosensors were developed from the synthesized metal oxide (MO) nanoparticles by supporting it on a gold electrode (Au). The activity of the developed nanosensor toward the detection of malaria biomarker (β-hematin) was determined and the optimum conditions at which the maximum detection and quantification occurred were established. β-Hematin current response at the sensors was higher when compared with the bare Au electrode and followed the order Au-CuO (C) > Au-CuO (M) > Au-Fe2O3 (M) > Au-Fe2O3 (C) > Au-Al2O3 (M) > Au-Al2O3 (C) > bare Au. The developed sensors were stable with a relatively low current drop (10.61–17.35 %) in the analyte. Au-CuO sensor had the best performance toward the biomarker and quantitatively detected P. berghei in infected mice's serum samples at 3.60–4.8 mM and P. falciparum in human blood serum samples at 0.65–1.35 mM concentration.